Under the henfluence : inside the world of backyard chickens and the people who love them - Danovich, Tove (Surrey Books, an imprint of Agate Publishing, 2023)
"An immersive blend of chicken-keeping memoir and animal welfare reporting by a journalist who accidentally became obsessed with her flock"--